PENGARUH PROFESIONALISME AUDIT, INTENSITAS MORAL UNTUK MELAKUKAN TINDAKAN WHISTLEBLOWING (STUDI PADA KAP DI INDONESIA) - Zanaria, Yulita (JURNAL AKUISISI, 2016)
Purpose â The purpose of this paper is to to investigate the influence ofÂ Â  professionalism auditor andÂ  intensity of moral Â toÂ  effect on whistleblowing actionÂ  ofÂ  KAPÂ  in IndonesiaDesign/methodology/approach-Â  The research method used is the population of all auditors who worked on 25 KAP in Indonesia. Sampling technique using nonprobabilitas or not random with convienience sampling method.Tool using regression analysis using F test and t test with SPSS ver.17.00. The paper ends with a set of hypotheses requiring further research.Â Findings â The paper finds that the professionalism auditor, intensity of moral Â simultaneously affect on whistleblowing actionÂ  ofÂ  KAPÂ  in Indonesia.Â  professionalism auditor variable partially significant affect on whistleblowing actionÂ  ofÂ  KAPÂ  in Indonesia. Variable intensity of moral Â has an effect on whistleblowing actionÂ  ofÂ  KAPÂ  in IndonesiaÂ Originality/value âThis paper provides influence ofÂ Â  professionalism auditor , intensity of moral , toÂ  effect on whistleblowing actionÂ  ofÂ  KAPÂ  in IndonesiaÂ Keywords: Professionalism auditor , intensity of moral , effect on whistleblowing action Â Paper type General review